갈색퍼짐병 발병토양의 미생물 군집 분석 - 이정한(Jung Han Lee); 민규영(Gyu Young Min); 전창욱(Chang Wook Jeon); 최수민(Su min Choi); 한정지(Jeong Ji Han); 심규열(Gyu Yul Shim); 곽연식(Youn-Sig Kwak) (Weed & turfgrass science, 2015)
Large patch, caused by Rhizoctonia solani AG2-2 IV, is a soil-born disease that is the most important of warm season turfgrass such as zoysia and Bermuda grass. This study was conducted to analysis of the soil microbial community structure on large patch. Center of the large patch (CLC), edge (CLE) and healthy (CLH) part of microbial communities were examined using metagenomics in Phylum level. Distribution trends of the rhizosphere microorganisms were similar to the order Proteobacteria, Acidobacteria, Chloroflexi, Firmicutes, Planctomycetes, Gemmatimonadetes, Nitrospira, Cyanobactria and Verrucomicrobia in soil collections. Contrastively Actinobacteria was more 56% abundant in healthy part soil (16%) than in the center (9.28%) or edge (10.84%) parts. Taxonomic distributions were compared among the CLC, CLE and CLH, total 6,948 OTUs were detected in the CLC, 6,505 OTUs for the CLE and 5,537 OTUs were detected in the CLE. Distributions of Actinobacteria OTUs were appeared 615 OTUs in the CLC, 709 OTUs in the CLE and 891 OTUs in the CLH. Among Actinobacteria, 382 OTUs were overlapped in the all soils. Not matched OTUs of CLH (286 OTUs) was detected 23 times higher than CLC (91 OTUs) and CLE (126 OTUs). 갈색퍼짐병은 토양 병원성균으로 Rhizoctonia solani AG2-2 IV가 원인균이다. 한국잔디나 버뮤다글라스와 같은 난지형 잔디에 가장 중요한 병으로 알려져 있다. 본 연구는 갈색퍼짐병 발병토양의 미생물 군집 분석으로 생물적 방제제로 이용할 근거자료를 수집하기 위하여 실시하였다. 갈색 퍼짐병의 중심부(CLC)와 가장자리(CLE), 건전부(CLH)에서 채취한 근권부 토양의 미생물 군집(bacterial composition)을 Metagenomics 데이터 분석으로 Phylum 수준에서 조사한 결과 미생물상은 Proteobacteria, Acidobacteria, Chloroflexi, Firmicutes, Planctomycetes, Gemmatimonadetes, Nitrospira, Cyanobactria, Verrucomicrobia, Bacteroidetes 등의 순으로 분포 경향은 모두 유사하게 나타났다. 이에 반해 Actinobacteria의 경우 중심부에서 9.28%, 가장자리에서 10.84%로 건전부에서의 16%에 비하여 5~6% 정도 높은 비율로 분포하는 결과가 나타났다. Phylum 수준에서 중복되는 미생물의 종류를 조사한 결과 전체적으로 중심부에서는 총 6,948 OTUs가 분포하였으며 가장자리와 건전부에서는 각각 6,505와 5,537 OTUs 분포하는 것으로 나타났다. Actinobacteria의 경우 중심부의 총 OTUs는 615였으며 가장자리와 건전부는 709와 891 OTUs로 나타났다. 또한 모두 중복되는 OTUs도 382로 높게 나타났으나 서로 중복되지 않는 OTUs는 건전부에서 286으로 중심부와 가장자리가 91과 126 OTUs인 것에 비하여 2~3배 이상으로 월등히 높게 나타났다.